2023
DOI: 10.24193/jebp.2023.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy: A Survey of the Public’s Ability to Recognize Mental Disorders and Their Knowledge about the Effectiveness of Helpful Interventions to Help the Victims

A. M. I. D. ABESINGHE,
K. P. D. K. I. KATUWAWELA,
K. P. W. LAKMALI
et al.

Abstract: "Background- Although Mental health literacy (MHL) among public has been widely studied in many countries, there are few studies on MHL in Srilanka. MHL is important as it is closely related to help seeking behavior and mental health outcomes. Poor MHL has been a major barrier on improving mental health care in Sri Lanka. The objective of this study was to describe MHL in terms of ability to recognize mental health problems, knowledge of helpful interventions and professional help available. The association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A type of MHL is depression literacy (D-Lit), which includes personal and general knowledge of depression and belief in its treatment ( 21 ). Studies have shown that most people have inadequate MHL ( 22 , 23 ). Most people do not know about psychological disorders, and they have a negative attitude toward their treatment or the effectiveness of treatment ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…A type of MHL is depression literacy (D-Lit), which includes personal and general knowledge of depression and belief in its treatment ( 21 ). Studies have shown that most people have inadequate MHL ( 22 , 23 ). Most people do not know about psychological disorders, and they have a negative attitude toward their treatment or the effectiveness of treatment ( 24 ).…”
Section: Introductionmentioning
confidence: 99%